Effects of occupational exposures on respiratory health in steel factory workers - Mozaffari, Sajjad; Heibati, Behzad; Jaakkola, Maritta S.; Lajunen, Taina K.; Kalteh, Safa; Alimoradi, Hadi; Nazari, Mahsa; Karimi, Ali; Jaakkola, Jouni J. K. (Frontiers in Public Health, 2023)
Background The steel factory work environment contains various chemical exposures that can affect indoor air quality and have impact on respiratory health of the workers. Aims The objective of this study was to assess potential effects of occupational exposures in steel factory workers in Iran on the respiratory symptoms, occurrence and the lung function levels. Method This was a cross-sectional study of 133 men working in a steel factory forming the exposed group and 133 male office workers forming the reference group from a steel company in Iran. The participants filled in a questionnaire and underwent spirometry. Work history was used both as dichotomous (exposed/reference) and a quantitative measure of exposure, the latter measured as duration of exposure in the specified work (in years) for the exposed group and zero for the reference group. Results Multiple linear regression and Poisson regression were used to adjust for confounding. In Poisson regression analyses, an increased prevalence ratio (PR) of all respiratory symptoms was observed in the exposed group. Lung function parameters were significantly reduced in the exposed group (p < 0.001). There was a dose–response relation between duration of occupational exposures and reduction in the predicted value of FEV1/FVC level (0.177, 95% CI −0.198 to −0.156) in all models. Conclusion The results of these analyses showed that occupational exposures in steel factory work increase the prevalence of respiratory symptoms and reduce lung function. Safety training and workplace conditions were found to need improvement. In addition, use of proper personal protective equipment is recommended.